PENGARUH CITRA DESTINASI DAN PENGALAMAN BERKESAN TERHADAP PEREKONOMIAN MASYARAKAT DAERAH WISATA GEOSITE SIPINSUR - Putri Laurensia Lumbantoruan; Nalom Siagian; Kepler Sinaga; Jonson Rajagukguk (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2026)
This study aims to analyze the influence of destination image (X1) and memorable experiences (X2) on the community's economy (Y) in the Sipinsur Geosite tourist area, Pearung Village, Humbang Hasundutan Regency. The population included MSMEs and tourists, with a sample of 96 respondents drawn using the Lemeshow formula and accidental sampling technique. Primary data were collected through questionnaires and analyzed using multiple linear regression using SPSS. The analysis results show a regression equation of Y = -3.528 + 0.620X1 + 0.417X2. A partial t-test proved that destination image had a significant positive effect (t=13.198; Sig=0.000 <0.05) and that effective experiences also had a significant effect (t=8.705; Sig=0.000 <0.05). A simultaneous F-test emphasized the joint influence of both variables (F=104.077; Sig=0.000 <0.05), with an R-square of 0.691 (69.1% of the variation in Y is explained by X1 and X2). It can be concluded that destination image and experiences have a positive and significant impact on the local economy of the Sipinsur Geosite. Management is advised to maintain the destination image and enhance the tourist experience to optimize the local economic impact.